Temperature-dependent optical properties of ice crystals in the far-infrared regime - Ren,T; Yang,P; Brindley,HE; L'Ecuyer,TS; Maestri,T (Geophysical Research Letters, 2025)
A database of temperature-dependent hexagonal ice aggregate optical properties in the far-infrared (FIR) spectrum is developed to support FIR missions, particularly the current Polar Radiant Energy in the Far InfraRed Experiment and the upcoming Far-infrared-Outgoing-Radiation Understanding and Monitoring. Based on this data set, simulations of the brightness temperatures (BTs) in the 100–667 cm−1 FIR region are conducted for an anvil-like ice cloud in a tropical atmosphere. The results show nonnegligible impact of ice cloud temperature on simulated BTs, which can be as large as 3 K due to the difference between fixed 160 or 270 K cloud temperature and the benchmark counterpart, varying in accordance with the ambient temperature profile for a cloud residing between 249.6 and 199.6 K. To enhance the accuracy of FIR radiative transfer modeling, it is recommended to incorporate temperature-dependent optical properties of ice clouds.